Defining indicators for disease burden, health outcomes, policies and barriers and facilitators to health services for migrant populations in the Middle East and North African region: a protocol for a suite of systematic reviews - Charles Agyemang; Ali Ardalan; Farah Seedat; Bouchra Assarag; Nuria Casamitjana; Kolitha Wickramage; Sally Hargreaves; Ana Requena-Mendez; Fouad M Fouad; Dominik Zenner; Anna Deal; Stella Evangelidou; et al. (BMJ Open)
Introduction The Middle East and North African (MENA) region is characterised by high and complex migration flows, yet little is known about the health of migrant populations, their levels of underimmunisation and access to healthcare provision. Data are needed to support regional elimination and control targets for key diseases and the design and delivery of programmes to improve health outcomes in these groups. This protocol describes a suite of seven systematic reviews that aim to identify, appraise and synthesise the available evidence on the burden and health outcomes, policies and access (barriers and facilitators) related to these mobile populations in the region.Methods Seven systematic reviews will cover three questions to explore the: (1) burden and health outcomes, (2) policies and (3) healthcare barriers and facilitators for the following seven disease areas in migrants in the MENA region: tuberculosis, HIV and hepatitis B and C, malaria and neglected tropical diseases, diabetes, mental health, maternal and neonatal health, and vaccine-preventable diseases. We will search electronic databases for studies in any language (year 2000–2023), reference-check relevant publications and cross-check included studies with experts. We will search for grey literature by hand searching key databases and websites (including regional organisations and MoH websites) for country-specific guidelines and talking to our network of experts for local and regional reports and key datasets. We will assess the studies and policies for their quality using appropriate tools. We will meta-analyse the data by disease outcome if they are of sufficient volume and similarity. Where meta-analysis is not possible and where data are on policy or access, we will narratively synthesise the evidence using summary tables, figures and text.Dissemination We anticipate disseminating the findings through peer-reviewed publications, conferences and other formats relevant to all stakeholders. We are following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and protocols will be registered on International Prospective Register of Systematic Reviews.